Hyaluronan and halogen‐induced airway hyperresponsiveness and lung injury. Issue 1 (23rd June 2020) - Lazrak, Ahmed; Song, Weifeng; Zhou, Ting; Aggarwal, Saurabh; Jilling, Tamas; Garantziotis, Stavros; Matalon, Sadis
Abstract: Chlorine (Cl2 ) and bromine (Br2 ) are produced in large quantities throughout the world and used in the industry and the sanitation of water. These halogens can pose a significant threat to public health when released into the atmosphere during transportation and industrial accidents, or as acts of terrorism. In this review, we discuss the evidence showing that the activity of Cl2 and Br2, and of products formed by their interaction with biomolecules, fragment high‐molecular‐weight hyaluronan (HMW‐HA), a key component of the interstitial space and present in epithelial cells, to form proinflammatory, low‐molecular‐weight hyaluronan fragments that increase intracellular calcium (Ca 2+ ) and activate RAS homolog family member A (RhoA) in airway smooth muscle and epithelial and microvascular cells. These changes result in airway hyperresponsiveness (AHR) to methacholine and increase epithelial and microvascular permeability. The increase in intracellular Ca 2+ is the result of the activation of the calcium‐sensing receptor by Cl2, Br2, and their by‐products. Posthalogen administration of a commercially available form of HMW‐HA to mice and to airway cells in vitro reverses the increase of Ca 2+ and the activation of RhoA, and restores AHR to near‐normal levels of airway function. These data have established the potential of HMW‐HA to be a countermeasure against Cl2 and Br2 toxicity. Abstract : In this review, we discuss evidence showing that the activity of Cl2 and Br2, and products formed by their interaction with biomolecules, can fragment high‐molecular‐weight hyaluronan—a key component of the interstitial space and also present in epithelial cells–to form proinflammatory, low‐molecular‐weight hyaluronan fragments, which leads to increased intracellular calcium and activated RAS homolog family member A in airway smooth muscle, epithelial, and microvascular cells.